2018
DOI: 10.1186/s12913-018-3685-6
|View full text |Cite
|
Sign up to set email alerts
|

Practice of emergency obstetric care signal functions and reasons for non-provision among health centers and hospitals in Lake and Western zones of Tanzania

Abstract: BackgroundThe Lake and Western Zones of Tanzania that encompass eight regions namely; Kagera, Geita, Simiyu, Shinyanga, Mwanza, Mara Tabora and Kigoma have consistently been reported with the poorest Maternal Newborn and Child Health (MNCH) indicators in the country. This study sought to establish the provision of Emergency Obstetric Care (EmOC) signal functions and reasons for the failure to do so among health centers and hospitals in the two zones.MethodsAll the 261 public and private hospitals and health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“… 17–19 A recent study in Tanzania has shown that there are large regional differences in health intervention coverage and these variations are related to differences in socioeconomic development and the strength of health systems among the regions of Tanzania. 64 …”
Section: Discussionmentioning
confidence: 99%
“… 17–19 A recent study in Tanzania has shown that there are large regional differences in health intervention coverage and these variations are related to differences in socioeconomic development and the strength of health systems among the regions of Tanzania. 64 …”
Section: Discussionmentioning
confidence: 99%
“…Maswanya and al. found out that policy restrictions, lack of supplies and professional development, and operating under lowly developed referral services were mentioned as the some of the drivers for low and inconsistent use of obstetric care services in western zones of Tanzania [47].…”
Section: Discussionmentioning
confidence: 99%
“…The target area, Shinyanga, is one of the regions which had higher maternal mortality than the national average (432/100,000 live births) in 2015 [ 38 ]. Shinyanga is one of eight regions – alongside Kagera, Geita, Simiyu, Mwanza, Mara, Tabora, and Kigoma – with the poorest reported maternal newborn and child health (MNCH) indicators in Tanzania [ 39 ]. Shinyanga is located in the northwestern part of Tanzania and consists of five Councils: three district councils (DC; Shinyanga, Kahama, and Kishapu); one municipal council (MC; Shinyanga), and one town council (TC; Kahama) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%